Emotional needs and the use of social networking website by adolescents - Pawłowska, Beata; Lekan, Monika; Międlar, Krzysztof; Biały-Międlar, Karolina; Fijałkowska, Paula; Landman, Marta (Current Problems of Psychiatry, 2012)
The aim of this work was to answer the following question: do any differences occur, if any, between emotional needs and activity shown by adolescents on Nasza Klasa [Classmates] social networking website?The examined group consisted of 279 junior high school and high school students aged 13-18 years, out of which a group of 240 students (169 girls and 71 boys) was singled out who had a profile on Nasza Klasa social networking website.In the research the following tests were used: the Socio-demographic Questionnaire designed by the authors, the Internet Addiction Assessment Questionnaire by Potembska and the Adjective Check List by Gough and Heilbrun in the version by Płużek.Results and conclusions:• The obtained results inform about statistically significant differences between the use of Nasza Klasa social networking website for the following purposes: making comments about photos of other people as well as submitting holiday photos and the intensified need for change, acquiring information about the others and the intensified need for deference, bragging and the intensified need for endurance, order and intraception, submitting family photos on the website and the need for nurturance, abasement and deference.• More than twice as many girls as boys have a profile on Nasza Klasa social networking website.